Effects of Learning with Ethnoscience Context on Learning Outcomes in Cognitive Aspects of Prospective Physics Teacher Students - Hikmawati Hikmawati; Sutrio; Wahyudi; Khaerus Syahidi (Postgraduate, University of Mataram, 2022)
Student learning outcomes in the cognitive aspect need attention because it is the professional competence of prospective teachers related to mastery of learning materials. The purpose of this study was to analyze the effects of learning in the context of ethnoscience on learning outcomes in the cognitive aspects of prospective physics teacher students. The research method used is quantitative with two stages. First, a limited trial study with a one-group pretest-posttest design at Hamzanwadi University with a total of 9 students. Second, experimental research with a post-test only group design was conducted at the University of Mataram, with a total of 77 students. In a limited trial study, an N-gain test analysis was carried out to determine the success rate of treatment with the minimum category being in the